The Use of Mindo (Mini Panggung Dongeng) Media in Students Speaking Skills - Kaffah, Silmi; Izzah, Lidiyatul (Indo Green Journal, 2023)
The aim of this research is to examine the use of MINDO (Mini Panggung Dongeng) as a media in teaching students' speaking abilities at MTs Al Ma'Mur. This research focuses on the difficulties that the students encountered and the advantages in the implementation of MINDO. This research is qualitative research, with a descriptive qualitative approach to describe in detail about the use of MINDO in students’ speaking skill. In order to gather the data, the researcher conducted observation and interviews in the 8th grade of MTs Al Ma’Mur Tangerang. After gathering the data, the researcher analyzed the data qualitatively. The results of the research showed that the difficulties faced by MTs Al Ma’Mur students are the lack of time allocation, the preparation of the puppets, noises from the students during the storytelling due to their excitement, and the unequal comprehension of the students after the story being told. The advantages include the students’ attention that was centered to the MINDO, the increase of students’ motivation and confidence in speaking, the interesting and fun learning process, and also the active learning process. Further research can be carried out by using CAR (classroom action research) in order to find the improvement on the implementation of MINDO in speaking skills regarding to the future directions.